PENGARUH POLA KOMUNIKASI ORANG TUA YANG SIBUK BEKERJA TERHADAP MOTIVASI BELAJAR ANAK PASCA PANDEMI (Survei Terhadap Siswa SMP Islam Malahayati) - Khairunnisa Indah Aryani, (2023)
Time management and communication between family members have become new problems after the pandemic. The length of time parents work causes a gap in interactions that occur between parents and children, which is feared to have an impact on children's learning motivation. This study aims to determine the effect of communication patterns of busy working parents on children's learning motivation after the pandemic. The type of research used is an explanatory quantitative research method. This research is survey-based and uses Berlo's Communication Theory which has elements of source, message content, media and receiver to analyze it. The data collection techniques used in this study to obtain research results, namely using a questionnaire or questionnaire to 142 respondents and FGD (Focus Group Discussion) to 8 respondents. Based on the results of the correlation test, the correlation coefficient of variable X1 on variable Y is -0.212 which means weak, while for variable X2 on variable Y, the result is 0.742 which means strong. The results of multiple linear regression calculations - 0.113 for variable X1 and 0.360 for variable X2 which means variable X1 has no influence while X2 has an influence on Y. The coefficient of determination shows the influence of variables X1 and X2 of 57.8% on variable Y. The results of the calculation in the hypothesis test show the X1 variable data of t count -2.805> t table 1.97718 and the significance is 0.006 <0.05. In the X2 variable, the t count is 13.142> t table 1.97718 and the significance is 0.000 <0.05. The results of hypothesis testing can be concluded that communication patterns have no influence on children's learning motivation while parents who are busy working have a significant influence on children's learning motivation.